2017
DOI: 10.1038/s41598-017-01888-w
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of dietary phytochemicals can predict their passive absorption in the human small intestine

Abstract: A diet high in phytochemical-rich plant foods is associated with reducing the risk of chronic diseases such as cardiovascular and neurodegenerative diseases, obesity, diabetes and cancer. Oxidative stress and inflammation (OSI) is the common component underlying these chronic diseases. Whilst the positive health effects of phytochemicals and their metabolites have been demonstrated to regulate OSI, the timing and absorption for best effect is not well understood. We developed a model to predict the time to ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 167 publications
1
37
1
Order By: Relevance
“…By contrast, T ½ showed a negligible correlation with TPSA (r = 0.010), low correlation with nrot (r = 0.329) and log P (r = 0.349) and a moderate correlation with Vol (r = 0.506) and MW (r = 0.528). These results were dissimilar to Selby-Pham et al 12 which observed moderate correlation for molecular weight and high correlation for log P and TPSA to T max following ingestion. Accordingly, physicochemical properties impacting inhalation pharmacokinetics were deemed to be different from those impacting ingestion pharmacokinetics.…”
Section: Biomatching Of Cannabis Phytochemicalscontrasting
confidence: 99%
See 3 more Smart Citations
“…By contrast, T ½ showed a negligible correlation with TPSA (r = 0.010), low correlation with nrot (r = 0.329) and log P (r = 0.349) and a moderate correlation with Vol (r = 0.506) and MW (r = 0.528). These results were dissimilar to Selby-Pham et al 12 which observed moderate correlation for molecular weight and high correlation for log P and TPSA to T max following ingestion. Accordingly, physicochemical properties impacting inhalation pharmacokinetics were deemed to be different from those impacting ingestion pharmacokinetics.…”
Section: Biomatching Of Cannabis Phytochemicalscontrasting
confidence: 99%
“…Table S3), with visualisation of either T max or T ½ with singular physicochemical measures (Figure 1) suggesting the possibility for non-linear relationships or the necessity for multiple measures to achieve predictive power. This is consistent with previous pharmacokinetic studies, such as the PCAP model, 12 which have shown that following consumption, individual measures had poor predictive power while a combination of measures could be used to achieve a model with greater predictive power. Pearson's correlation coefficients (Supplement Table S2) were used to assess the power of physicochemical properties to predict pharmacokinetic properties based on the categorisation of strength of correlation as; r < 0.3 negligible, 0.3 < r < 0.5 low, 0.5 < r < 0.7 moderate, 0.7 < r < 0.9 high and r > 0.9 very high.…”
Section: Biomatching Of Cannabis Phytochemicalssupporting
confidence: 91%
See 2 more Smart Citations
“…As phytochemicals are recognised by the human body as xenobiotics, their presence in the human body is transient [ 40 ] and influenced by their physicochemical properties. Recently, we have developed the phytochemical absorption prediction (PCAP) model, allowing direct calculation of the time required for phytochemicals to reach their maximal plasma concentrations (T max ) after oral consumption, based on their molecular mass and lipophilicity descriptor log P [ 41 ]. Further, a liquid chromatography mass spectrometry (LC-MS) method has been developed to characterise T max ranges of phytochemical mixtures based on molecular mass and log P [ 42 ].…”
Section: Introductionmentioning
confidence: 99%